"A garden had been left to grow wild there": considering nature in Ivan Vladislavić's Johannesburg. Issue 1 (2nd January 2017) - Manià, Kirby
Abstract: Johannesburg has frequently been subjected to critical examinations that conceive the city as a metropolis dominated by late capitalist excess and gold mining hyperbole. Along these particular lines, much of the literary scholarship that considers Vladislavić's city texts have focussed on his conception of the built environment that critiques its exploitative extractive history and its simulacral tendencies. However, sustained critical attention of his treatment of nature in the urban space has largely been neglected or underplayed. The natural Highveld environment, for Vladislavić, occupies a fraught and liminal space in the city, pushed to the margins of a brutalizing modernity. Nature in Johannesburg, he opines, is a construction, an imposition and inheritance that belies the city's colonial and European settler history. However, there are moments in which, when human attention is turned away, nature in its untended and generative capacity works to unmake the structural obduracy of the settled city. This manifests in episodes that embrace the quiet potency of wild gardens that disrupt the urban status quo.